Alveolar-type rhabdomyosarcoma of nasal cavity and paranasal sinus in adult with pulmonary metastasis: A case report - S., Rajinder; J., Rohaizam; M., Irfan (Elsevier, 2016)
Alveolar-type rhabdomyosarcoma of head and neck region in adult is extremely rare. We report a case of a 33-year-old lady who presented with persistent right unilateral nasal obstruction and epistaxis for one months’ duration. Examination showed a fleshy, irregular-surfaced mass occupying the whole right nasal cavity and histopathological examination revealed alveolar-type rhabdomyosarcoma. Metastatic work-up showed pulmonary metastasis. After 3 months following completion of four cycles of chemotherapy, a repeated scan showed significant shrinkage of the tumor.